1996
DOI: 10.1111/1523-1747.ep12328031
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Fully Hydrated Human Stratum Corneum: A Freeze-Fracture Electron Microscopy Study

Abstract: The structure of fully hydrated human stratum corneum was investigated by means of freeze-fracture electron microscopy. Mammary and abdominal stratum corneum were incubated for 48 h with phosphate-buffered saline, pH 7.4, occlusively or phosphate buffer, pH 7.4, occlusively and non-occlusively. The micrographs showed the corneocytes aligned parallel to the surface of the stratum corneum embedded in intercellular lipids. The corneocytes were swollen by the uptake of water. New features located in the intercellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 37 publications
9
52
0
Order By: Relevance
“…17 mm; Agache 2004), the SC at the volar forearm cannot pull effectively against its connection with the dermis, explaining that macroscopically no skin wrinkling was observed by thorough visual inspection after immersion. Morphological and structural changes of the SC due to water uptake or water exposure are well documented in the literature (Querleux et al 1994;Rawlings et al 1995;Van Hal et al 1996;Norlén et al 1997;Warner et al 1999Warner et al , 2003Sato et al 2000;Bouwstra et al 2003;Richter et al 2004). For example, a twofold reduction in the skin surface roughness (Sato et al 2000), as well as SC swelling of approximately 8% in the area dimension and 26% in the thickness dimension, has been observed under water treatment ( Norlén et al 1997).…”
Section: Water and The Sc: Skin Wrinkling Morphology And Molecular Cmentioning
confidence: 92%
See 2 more Smart Citations
“…17 mm; Agache 2004), the SC at the volar forearm cannot pull effectively against its connection with the dermis, explaining that macroscopically no skin wrinkling was observed by thorough visual inspection after immersion. Morphological and structural changes of the SC due to water uptake or water exposure are well documented in the literature (Querleux et al 1994;Rawlings et al 1995;Van Hal et al 1996;Norlén et al 1997;Warner et al 1999Warner et al , 2003Sato et al 2000;Bouwstra et al 2003;Richter et al 2004). For example, a twofold reduction in the skin surface roughness (Sato et al 2000), as well as SC swelling of approximately 8% in the area dimension and 26% in the thickness dimension, has been observed under water treatment ( Norlén et al 1997).…”
Section: Water and The Sc: Skin Wrinkling Morphology And Molecular Cmentioning
confidence: 92%
“…For example, a twofold reduction in the skin surface roughness (Sato et al 2000), as well as SC swelling of approximately 8% in the area dimension and 26% in the thickness dimension, has been observed under water treatment ( Norlén et al 1997). Prolonged exposure to water leads to thickening of the SC resulting from corneocyte swelling (threefold after 4 hours, fourfold after 24 hours) and the storage of water-soluble substances in intercellular cisternae (Van Hal et al 1996;Warner et al 2003). These water-related changes in the SC present a dynamic dimension of the brick-and-mortar model (Elias 1983), being able to adapt to external stress factors such as overhydration (Praessler & Fluhr 2005).…”
Section: Water and The Sc: Skin Wrinkling Morphology And Molecular Cmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also found that increased skin hydration may result in swelling and opening of the compact structure of the SC, leading to an increase in penetration of drugs. 13,29) On the contrary, numerous papers concluded that skin hydration does not correlate with skin permeability. Although the use of solid nanoparticles increased skin hydration to a level similar to that achieved with the use of an ointment, the permeation rate of tacrolimus in a lipid nanoparticle formulation was almost 16-21 times higher than that of an ointment formulation.…”
Section: )mentioning
confidence: 99%
“…A second possible explanation for this short path length is that the SC pore pathways may be interrupted by pools of water that can be described as a collection of thin barriers with water reservoirs in-between. This multibarrier heterogeneous SC model is supported by the observation of water reservoirs in the SC intercellular space after skin hydration (26,27), in which the interconnected aqueous reservoirs become part of the barrier structure in fully hydrated HEM (3). Another possible explanation is that the homogenous membrane model is not applicable for the case when intrinsic membrane properties are altered due to transmembrane electrical potential (19), and therefore does not adequately describe AC iontophoresis at 2.5 V. Transdermal iontophoretic transport could deviate from the homogenous membrane model at 2.5 V due to the latter two explanations alone or a combination of all three explanations.…”
Section: Discussionmentioning
confidence: 68%